VOICE OF A HYBRID SPEAKING FROM A DISCRETE CULTURAL POSITION IN THE NOVEL CEREMONY BY LESLIE MARMON SILKO - Sangeeta Jhajharia; Mamta Beniwal (Soegijapranata Catholic University, 2011)
The literature of post colonialism is a literature of marginality and liminality, portraying characters caught between one culture and another. The work represents a deep cultural conflict in the mind of an American who is from mixed ancestry. Ethnic nationalism and the recovery of traditional culture a classic formulation: A group withdraws into itself and labels the historically oppressive culture as the enemy. The nation or group feels that its social oppression is inextricably tied with the destruction of its traditional culture. To recover an aspect o/the suppressed culture - even as fantasy - can be an act not only 0/ revival but of subversion, a way of reifying the oppressed group sense o/separateness and entitlement.